Pemanfaatan Teknologi Penginderaan Jauh dan Sistem Informasi Geografis untuk Pendugaan Potensi Peresapan Air DAS Wedi Kabupaten Klaten-Boyolali - Agus Anggoro Sigit (Universitas Muhammadiyah Surakarta, 2011)
The study was conducted in Klaten-Boyolali regencies in Wedi Watershed which is the Watershed of Dengkeng. The study aimed to: 1) know the interpretation precision of black and white panchromatic air photo scaling 1: 50.000 in identifying the soil factor, slope, landuse, vegetation density, and land conversation, related to the influences toward potensial water infiltration in the area of study; and 2) to know the distribution of potensial water infiltration in the area of study and analyze to the spatial distribution. The method of the study used was air photo interpretation supported by limited survey for filed test. The method of analysis applied was spatial analysis using Geographical Information System Technology (GIS). The result of the study showed that: 1) the level of air photo for interpreting determination factor of water infiltration in the area of study is acceptable together with the precision level of: slope 89.47%; soil texture 82.14%; land use 90.16%; vegetation density 88.89%; and land conservation 80.88%. it meant that although the precision level achieved had not been included in very precise category, the air photo still can be used in this study; 2) the potensial of water infiltration in the area of study tended to be less good, indicated by the dominance of the land in status of ‘begin to be rather critical and critical’ in the width of 81.999 km² or 75.04% placed by 28 land units; while the remaining of 8 land units in the width of 3.154 km² or 20.62% was in the status of 'natural normal' and 14 land units in the width of 22.544 km² or 20.62% had ‘good’ status. In the area of study, the space of land units with the potensial of good infiltration had no spatial relevance to the space of land units and the great infiltration capability.